Distal junctional kyphosis in patients with Scheuermann’s disease: a retrospective radiographic analysis - Ghasemi, Amir; Stubig, Timo; Nasto, Luigi A.; Ahmed, Malik; Mehdian, Hossein (Springer Verlag, 2016)
Purpose